Comparison of behaviour of laterally loaded round and squared timber bolted joints (Fracture and Structural Integrity, 2016)
In the current European standards for design of timber structures, the issue of timber-to-timber joint type is addressed only to squared timber, which makes the pinpointing of the round timber bolted joints load carrying capacity near-unfeasible due to the insufficient support in the current standards. There have been made series of tests of round timber joints in different inclinations of the loading force and also the reference tests of squared timber joints to compare the behaviour of this type of joints. Mechanical behaviour of the round and the squared timber bolted joints was tested in the laboratory of the Faculty of Civil Engineering in Ostrava. This paper presents results of static tests in tension at an angle of 0°, 90° and 60° to the grain of squared and round timber bolted joints. Load carrying capacity was determined according to the applicable standards and theories of fracture mechanics. The test results of laboratory tests were then compared with the results of theoretical calculations.
Keywords: Round timber; Bolt; Joint; Load carrying capacity